Fronteras geográficas y simbólicas: el espacio mediterráneo valenciano en la literatura y en el arte - Macciuci, Raquel (2010)
The vast southern European coast is inhabited by a great number of communities whose lifestyles and culture have, since time immemorial, been closely linked to the Mediterranean sea, a decisive territory, both geographic and symbolic. At the same time, each of these populations have developed particular identity marks within the framework of their specific historical and geographic coordinates. The purpose of this work is to focus on a specific Spanish Mediterranean region, Valencia, and to attempt a hypothesis about the importance of the mediterranean context in the process by which their collective identity has been built. Starting from the analysis of both a series of literary and pictorial references and of aesthetic and ideological debates -all of them belonging to the Valen- cian culture-, this article alms to study the diversity and the continuity of a southern European frontier, which has been constantly vanishing and reappearing on the time-line as well as on the surface of the maps.